By its cover - Leon, Donna (Leon, Donna. Commissario Guido Brunetti mystery., 2014)
One afternoon, Commissario Guido Brunetti gets a frantic call from the director of a prestigious Venetian library. Someone has stolen pages out of several rare books. After a round of questioning, the case seems clear: the culprit must be the man who requested the volumes, an American professor from a Kansas university. The only problem--the man fled the library earlier that day, and after checking his credentials, the American professor doesn't exist. As the investigation proceeds, the suspects multiply. And when a seemingly harmless theologian, who had spent years reading at the library turns up brutally murdered, Brunetti must question his expectations about what makes a man innocent, or guilty.